Morphology and characterization of synthesized hybrid organosilica materials incorporating a biphenyl moiety - Virtudazo, Raymond V. Rivera (2006)
The study focuses on the characterization of a synthesized hybrid mesoporous organosilica material incorporating a biphenyl moiety using the surfactant-mediated polymerization approach. In the lieu of a new material, the parameters of the modified polymerization process such as aging time (autoclave time) and surfactant cetyltrimethylammonium bromide CTAB concentration were investigated and optimized to obtain a mesoporous organosilica material with sufficient surface area. The making of a new mesoporous material with a narrower pore size distribution range (20 A-500 A) was also evaluated. This would be useful in utilizing the product as metal and chiral center for catalysis and other potential applications such as sensing, separation and microelectronics. Characterizations of the structures, organic functionalities and surface morphologies of the newly prepared mesoporous organosilica were performed using powder X-ray Diffraction (XRD), Scanning Electron Microscopy (SEM), Transmission Electron Microscopy (TEM), Differential Scanning Calorimetry (DSC), FT-IR and nitrogen adsorption/desorption experiments. Results showed that a wide spectrum of unique primary particles morphologies of mesoporous organosilica incorporatin biphenyl moiety consisting of spindle-, rod-, and platelike particles and nanoparticles were produced by tuning synthetic parameters such as stirring and autoclaving time. The results were compared to the existing data on hybrid organosilica materials. These primary particles were found to self-assemble in solution to form various large hierarchical macrostructures, such as meso-structured necklaces and cobweb-supported necklaces. Stirring, reaction time, and autoclaving were identified to be the key factors affecting the efficiency and degree of the self assembly process. The resulting mesoporous organosilica produced in this study had interplaner spacing between 8 to 9 nm as revealed by XRD, specific surface area from 1196.99-1578.57 m2g-1, total pore volume from 1.2-0.75 cc/g (pore smaller than 20.0 nm) and primary pore diameter (BJH desorption method) from 3.54-3.56nm. DSC data showed that the synthesized mesoporous organosilica exhibited relative thermal stability in air in the range of 180-200 degree celcius.